Comunicación multimedia y su relación con el desarrollo cultural en los adolescentes del sector Playa Grande, ciudad de Quevedo, año 2019 - George Ronquillo, Evelin Lisseth (2020)
In the present investigation, the main objective is to design information workshops on the good use of multimedia communication media and their contribution to the cultural development of adolescents in the sector, since currently new technologies are part of people's daily lives and they have caused a social and cultural impact due to their immediacy and ease of access to them. The use of multimedia media, have become indispensable for human beings especially for adolescents, who from an early age use them without knowing the negative effects that they can cause due to their bad and excessive use, through the workshops Try to make teenagers aware that they use multimedia communication for positive effects in their lives and in this way foster culture in their sector and have excellent knowledge about their origins, customs and culture, since cultural development is important for society. It should be noted that multimedia communication is carried out through images, videos, audios among others, therefore it has become a means by which people can stay informed, entertained, and in turn use their creativity and imagination, for this reason the communication is more fluid and it is considered that through this, strategies are proposed that benefit adolescents and the sector since cultural identity is in crisis and is reflected in the Playa Grande sector of the city of Quevedo.